2013
DOI: 10.5120/12130-8506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Data Preprocessing on Software Effort Estimation

Abstract: Software effort estimation requires high accuracy, but accurate estimations are difficult to achieve. Increasingly, data mining is used to improve an organization's software process quality, e.g. the accuracy of effort estimations .There are a large number of different method combination exists for software effort estimation, selecting the most suitable combination becomes the subject of research in this paper. In this study, three simple preprocessors are taken (none, norm, log) and effort is measured using C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Some works [17,19,37] employ LD or PD technique to tackle the missing data problem. In [20,26,21], the researchers concluded that the imputation strategy is more helpful for improving the estimation performance as compared with deletion and ignoring strategies.…”
Section: Solutions For Missing Data Problem In Seementioning
confidence: 99%
See 3 more Smart Citations
“…Some works [17,19,37] employ LD or PD technique to tackle the missing data problem. In [20,26,21], the researchers concluded that the imputation strategy is more helpful for improving the estimation performance as compared with deletion and ignoring strategies.…”
Section: Solutions For Missing Data Problem In Seementioning
confidence: 99%
“…Considering the noisy, redundant, or unreliable information in dataset, like in [17], we employ the z-score normalization [56] to preprocess data. For a variable x with mean  and standard deviation  , the normalized variable using z-score normalization can be represented as:…”
Section: Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Pada software metric terdapat atribut sebagai skala pengukuran perangkat lunak yaitu: memberikan pemahaman dan mampu dibaca oleh setiap anggota pengembang [15]. Keempat parameter ini akan diklasifikasikan dengan algoritma K-Nearest Neighboor sehingga didapat mana yang berpengaruh dalam pengujian dan pengukuran perangkat lunak agar bebas cacat.…”
Section: Iunclassified